Philosophy of environmental management systems according to ISO 14001 in Poland - Czartoszewski, Jacek W. (Studia Ecologiae et Bioethicae, 2004)
The author discusses attributes, requirements, and effects which was ligated by application environmental management systems and presents putting in practice ISO 14001 in Poland. The author considers also philosophical bases of sustainable development idea and philosophy of Total Quality Management [TQM ] and British norms BS 7750.